Smart multi-functional micro-hub for neighborhoods: sustainable mobility and environmental restoration in hig-density social neighborhoods. - Rosa-Jiménez, Carlos; Prados Gómez, Carlos (Saint Petersburg State University of Architecture and Civil Engineering, 2022)
Introduction: Outdoor car parks have been a common and cost-effective solution to solve private mobility in European social housing districts built between 1960 and 1980, but it has significant, particularly environmental and spatial, impacts. The future of urban mobility requires a change to an electrified community model, based on shared vehicle fleets. The purpose of the study was to analyse the transport, social and environmental improvements of the smart multifunctional micro-hub for neighbourhoods, a theoretical proposal designed to facilitate the transition towards a decarbonised city. Methodology: The literature is therefore reviewed and a case study in the city of Malaga is provided. The results show, on the one hand, the environmental, economic and spatial advantages of this model compared to the traditional underground car parks. On the other hand, it proposes the design characteristics to be adopted by this type of buildings and their urban space. Finally, the article discusses the implications of setting up a citywide network of micro-hubs and the ensuing benefits.
Política de acceso abierto tomada de: https://aej.spbgasu.ru/index.php/AE/about/editorialPolicies#openAccessPolicy
Keywords: Transporte sostenible; Aparcamientos; Automatic parking system; Green parking; Car sharing; Public transport; Active facades